1993
DOI: 10.1193/1.1585726
|View full text |Cite
|
Sign up to set email alerts
|

Slotted Bolted Connection Energy Dissipators

Abstract: Slotted Bolted Connections (SBCs) are modified bolted connections designed to dissipate energy through friction during rectilinear tension and compression loading cycles. Experimental results on two types of SBCs are reported. In one type, friction occurs between clean mill scale steel surfaces; in the other, friction is between clean mill scale steel and brass surfaces. The behavior of connections with brass on steel frictional surfaces is found to be more uniform and simpler to model analytically than that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
142
0
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(150 citation statements)
references
References 0 publications
4
142
0
4
Order By: Relevance
“…It could be concluded that it can be assumed that all damping coefficients are equal, leading to reduce the damping coefficient selection problem to a one-dimensional problem. 24,25 Exhaustive search approach attempts to solve numerical problems in which generate and inspect all data configurations in a large state space that is ensured to include the desired solutions and investigate all possible combinations of number of dampers locations. The mentioned strategy is provided to be globally optimum, but it is an extremely time consuming procedure.…”
Section: Exhaustive Search Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It could be concluded that it can be assumed that all damping coefficients are equal, leading to reduce the damping coefficient selection problem to a one-dimensional problem. 24,25 Exhaustive search approach attempts to solve numerical problems in which generate and inspect all data configurations in a large state space that is ensured to include the desired solutions and investigate all possible combinations of number of dampers locations. The mentioned strategy is provided to be globally optimum, but it is an extremely time consuming procedure.…”
Section: Exhaustive Search Methodsmentioning
confidence: 99%
“…21 Among the dissipation systems, friction dampers with various designs were expanded and exerted for the seismic protection, as their hysteretic behaviors could be kept stable for cyclic loads and desirable slip loads are easily acquired by regulating normal forces acting perpendicularly to a friction surface, as well as their simple energy dissipation mechanism and easy manufacturing, installation, and maintenance. [22][23][24][25][26] Piezoelectric actuators are especially interesting due to their high response velocity, low energy demand, compact size, and appropriate functionality within a broadband frequency range. 27 Because of that, several scholars have studied about piezoelectric friction dampers to enhance damping in seismic isolation systems and in combination with tuned mass dampers.…”
Section: Introductionmentioning
confidence: 99%
“…-Reported experiments (Tyler 1985, Filiatrault and Cherry 1987, Fitzgerald et al 1989, Anagnostides and Hargreaves 1990, Aiken and Kelly 1990, Richter et al 1990, Whittaker et al 1991, Grigorian et al 1993, Yang and Popov 1995, Wu and Ou 2003, Morgen and Kurama 2004, Ng and Xu 2006, Vial et al 2005, Ricles et al 2006, Zhu et al 2006, Tsai et al 2008, Morgen and Kurama 2008, Iyama et al 2009) do not yield enough information about those questions, as they are mostly oriented to check the global validity of particular devices or assemblies. -The numerical simulation constitutes a challenging issue as the dynamic behavior of friction devices is highly nonlinear, as discussed previously.…”
Section: Fig 2 Hysteresis Loops Of Energy Dissipatorsmentioning
confidence: 99%
“…A variety of friction dissipators have been proposed for structural energy dissipation (Pall and Marsh 1982, Palsson et al 1984, Tyler 1985, Sumitomo 1987, Pall 1989, Richter et al 1990, Vezina et al 1992, Cherry and Filiatrault 1993, Grigorian et al 1993, Way 1996, Soong and Dargush 1997, Housner et al 1997, Wu and Ou 2003, Cho and Kwon 2004, Morgen and Kurama 2004, Tsai et al 2008, Morgen and Kurama 2008, design criteria have been issued (Rao et al 1996, Colajanni and Papia 2008, Levy et al 2000, Moreschi and Singh 2003, De la Llera et al 2005, Levy, Lavan and Rutenberg 2005, numerical simulation algorithms have been formulated (Dimova et al 1995, De la Cruz et al 2007) and a number of applications have been reported (Pall et al 1993, Tena 2007, Zhou et al 2007). In the reference (Dimova and Hirata 2000) a study about the seismic efficiency of friction dissipators is presented.…”
Section: Fig 2 Hysteresis Loops Of Energy Dissipatorsmentioning
confidence: 99%
“…There were, however, problems in bolt-elongation methods, as it was impossible to repair and restore the leg-joint where anchor-bolts had already elongated so that in order to make the deformed structure restored, large scale concrete dismantling money consuming work had to be required.Therefore, I proposed a new method for giving higher stiffness and rich ductility to LSB joint system by making use of Slotted Bolted Connection (SBC) method [5]. Figure 5 shows a global concept of moment-resisting joint assembled with LSB joint system modified using SBC system [6].…”
Section: Rigid and Ductile Lsb Joint Systemmentioning
confidence: 99%